PHYTOCHEMICAL CONTENT AND ANTIOXIDANT ACTIVITY IN TRADISIONAL BALINESE BABI-GULING SPICES - Indraguna Pinatih, G N; Suryadhi, NT; Santosa, A.; Muliartha, IKG (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
The traditional Balinese richly spiced swine-grill (Babi-guling) has been increasingly popular even among both the domestic and foreign tourists. The traditional grill is very unique in taste as it contains two main components, i.e. the pork and the unique Balinese spices, which probably could work antagonistically one against the other in affecting people health. The pork because of its rich content of saturated fatty acid is a risk of atherosclerosis, while the spices appear to be rich in antioxidatns. This is a preliminary atherosclerosis experimental study designed to screen qualitatively the phytochemical contents of the spices and to test their antioxidant activity and strength in different concentrations in vitro. The methods used included Willstater test, NaOH 10% test, Meyer test, Leiberman-Burchard test, test for saponin, and test for phenol. The antioxidant activity was estimated by using DPPH (2,2-diphenyl-1-pricrylhydrazyl) test. The treatment applied to the spice before testing was raw and cooked by heating it inside the pig’s body cavity. The concentrations of spices tested were 100, 1000 and 8000 ppm. The results of our study revealed that the phytochemical content of the spices were flavonoids, terpenoids and phenolic compounds, but saponin and alkaloids were not detected. The antioxidant activity was ineffective in concentration of 100 ppm (percentage of reduction < 50%), effective in concentration of 1000 ppm (percentage of reduction 50-60%), and too thick in concentration of 8000 ppm (percentage of reduction >100%. We inferred that the traditional Balinese richly spiced swine-grill contains flavanoids, terpenoids and phenol which can act as antioxidants in vitro, and the most effective concentrations to decrease the free radicals were between 1000-8000 ppm.
Keywords: Traditional Balinese spices, flavonoids, terpenoids, phenol, antioxidant activity